2019
DOI: 10.1111/bpa.12781
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial ependymomas: molecular insights and translation to treatment

Abstract: Ependymomas are primary central nervous system tumors (CNS), arising within the posterior fossa and supratentorial regions of the brain, and in the spine. Over the last decade, research has resulted in substantial insights into the molecular characteristics of ependymomas, and significant advances have been made in the establishment of a molecular classification system. Ependymomas both within and between the three CNS regions in which they arise, have been shown to contain distinct genetic, epigenetic and cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 104 publications
0
20
0
Order By: Relevance
“…Recent large-scale genomic sequencing studies have identified distinct subgroups of Supratentorial (ST)-Ependymoma, characterized by distinct methylation and gene expression patterns and the presence of characteristic gene fusion products that represent the likely tumor-initiating events and oncogenic drivers in these tumors (Lester & McDonald, 2020;Pajtler et al, 2015;Parker et al, 2014).…”
Section: Modeling Of Less Common Cns Tumorsmentioning
confidence: 99%
“…Recent large-scale genomic sequencing studies have identified distinct subgroups of Supratentorial (ST)-Ependymoma, characterized by distinct methylation and gene expression patterns and the presence of characteristic gene fusion products that represent the likely tumor-initiating events and oncogenic drivers in these tumors (Lester & McDonald, 2020;Pajtler et al, 2015;Parker et al, 2014).…”
Section: Modeling Of Less Common Cns Tumorsmentioning
confidence: 99%
“…When the pathway is disabled, the oncoprotein can translocate to the nucleus and interact with several transcription factors, causing increased cellular replication and reduced apoptosis. 10…”
Section: Classificationmentioning
confidence: 99%
“…Typically, they are believed to arise from the ependymal lining of the ventricles, cerebral hemispheres and central canal of the spinal cord. Intracranial ependymomas are rare primary tumors, accounting for 2.5% of all intracranial gliomas and 7% of primary central nervous system tumors diagnosed annually [ 1 , 2 ]. They account for 5–12% of brain tumors in children and 1–3% of brain tumors in adults [ 1 , 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…They account for 5–12% of brain tumors in children and 1–3% of brain tumors in adults [ 1 , 3 , 4 ]. The incidence of ependymomas is estimated to be 0.43 patients per 100,000 population [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%